Desenvolvimento de plataforma de simulação de sistema de automação baseado em tecnologias livres - Oliveira, Guilherme Lawrence Rebouças (2020)
The rapid dissemination of automation makes it an increasingly interesting tool diverse entities, from large industries to offices that seek Efficient energy use and comfort for their employees. However, the development of automation and supervision projects is often limited by the lack of alternatives to proprietary software, which can represent high costs that can make them nonviable, in addition to having limited compatibility with other devices. This work aims to propose the implementation of an automation system using open technologies only, such as python modules and Modbus protocol. This is done through the development of a program that simulates an electrical system and its components in a communication network and communicates with the free software ScadaBR. The proposed use and the developed codes can be adapted to different contexts which can enable the development of low cost applications in several areas.